Ukusebenza/Ukuphangela: Raiding the Work of the Future. - Helena, Pohlandt-McCormick; Minkley, Gary (Kronos: Southern African Histories, 2024)
This paper is not about work or labour itself, and how it changes historically in South Africa (from pastoral, to agricultural and industrial; native labour, wage labour, migrant labour etc.), but about how the meaning of 'work' and 'labour' itself changes. What we want to suggest, is that an 'original' meaning of the tasks/duties associated with 'work' was 'woman': ukusebenza. What men did, does not constitute 'work' but something else entirely: raiding, moving, occasional, going etc.: ukuphangela. It is in the latter term, ukuphangela, that the term 'raid' emerges, and the argument draws on this notion and meaning of raid to underscore the re-thinking of gender, the subject and her relation to work, and history. The paper operates in two registers, focusing on the historic meanings of work and labour in the Eastern Cape and tracing lateral translations of these meanings into East London in the 1950s. It argues that in re-thinking meanings of labour and work through multiple temporalities, and through the contested meanings of the isiXhosa terms ukusebenza and ukuphangela, these word fragments are read as 'entryways to a wordliness' that puts lateral universals and temporalities of work back into circulation. As such, we pose the question rather, following Anne Kelk Mager and Helen Bradford, of whether it is gender (and what it means to be a man or a woman) that is at the forefront not only of class and race struggles, but of what comes to constitute the meaning of 'work', a concept whose provenance and meaning changes, as we have noted, with the making of modernity, industrialisation/capitalism, and the 'Europeanisation' of the world.